Motivating children to learn the Arabic language through classic Arabic books - Sya'diah, Marliana; Hamidah; Anshari, Muhammad Redha (Institut Agama Islam Negeri Palangka Raya, 2024)
This research aims to determine: (1) Al-Qur'an literacy activities (2) Children's motivation to learn Arabic through classic Arabic books and (3) Barriers to Al-Qur'an literacy activities. This research is descriptive in nature with a qualitative approach. The results of the research show that (1) The activities carried out at Madrasah Diniyah Sidomulyo are Al-Qur'an literacy activities which consist of practicing reading the Al-Qur'an, makharijul letters, and recitation knowledge. Meanwhile, for learning Arabic, we use standard classical Islamic boarding school books, including Ta'lim muta'alim, al-jurumiyah, at-Tasrif and aqidatul awwam. (2) The motivation for children to learn Arabic at Madrasah Diniyah Sidomulyo is divided into 2, namely intrinsic motivation which is influenced by the child's drive and need to learn and the desire to successfully master Arabic, because of the hopes and aspirations of becoming an Arabic teacher. And extrinsic motivation is based on interesting learning activities and a conducive learning environment. (3) The implementation of Al-Qur'an literacy activities at Madrasah Diniyyah is hampered due to a lack of teachers, students are not yet accustomed to using classic Islamic boarding school books, resulting in difficulties in learning. Lack of facilities and infrastructure such as management rooms, teaching rooms, administration rooms and libraries.